Maintenance of efficacy and safety with subcutaneous golimumab among patients with active rheumatoid arthritis who previously received intravenous golimumab. - Taylor, P; Ritchlin, C; Mendelsohn, A; Baker, D; Kim, L; Xu, Z; Mack, M; Kremer, J (2011)
OBJECTIVE: To evaluate the efficacy/safety of subcutaneous (SC) golimumab in patients with rheumatoid arthritis (RA) who previously received intravenous (IV) golimumab with or without methotrexate (MTX). METHODS: Adult patients with RA (n = 643) with persistent disease despite MTX (≥ 15 mg/wk for ≥ 3 months) were randomized to IV placebo + MTX (n = 129) or IV golimumab 2-4 mg/kg (± MTX) every 12 weeks (n = 514). Patients who completed the study through Week 48 could participate in the longterm extension (LTE), comprising open-label golimumab 50 mg SC every 4 weeks (± MTX) for 24 weeks (LTE-0 to LTE-24) followed by 16 weeks of safety followup (LTE-24 to LTE-40; MTX could be adjusted). RESULTS: At Week 48, 28% (nominal p < 0.001 vs placebo), 11%, and 8% of patients who received IV golimumab + MTX, golimumab alone, and placebo + MTX, respectively, achieved ≥ 50% improvement in the American College of Rheumatology response criteria (ACR50). Among the 505 patients who entered the LTE and were still participating, the proportion of patients treated with golimumab 50 mg SC (± MTX) achieving an ACR50 response increased to 44% at both LTE-14 and LTE-24. ACR20, ACR70, and 28-joint Disease Activity Score using C-reactive protein exhibited similar response patterns as ACR50. Infections were the most commonly reported adverse events through the end of IV golimumab dosing (37% placebo + MTX, 45% golimumab, 51% golimumab + MTX) and with SC golimumab from LTE-0 through LTE-40 (35% golimumab, 36% golimumab + MTX). Concomitant MTX use yielded lower incidences of antibodies to SC golimumab and injection-related reactions. CONCLUSION: Clinical improvements observed in golimumab-treated patients were sustained or improved in patients switched from IV (2-4 mg/kg ± MTX) to open-label SC (50 mg ± MTX) golimumab. Both IV and SC golimumab demonstrated acceptable safety profiles (Clinicaltrials.gov NCT00361335).